2004
DOI: 10.1128/jb.186.21.7196-7204.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Escherichia coli AaeAB Efflux Pump: a Metabolic Relief Valve?

Abstract: Treatment of Escherichia coli with p-hydroxybenzoic acid (pHBA) resulted in upregulation of yhcP, encoding a protein of the putative efflux protein family. Also upregulated were the adjacent genes yhcQ, encoding a protein of the membrane fusion protein family, and yhcR, encoding a small protein without a known or suggested function. The function of the upstream, divergently transcribed gene yhcS, encoding a regulatory protein of the LysR family, in regulating expression of yhcRQP was shown. Furthermore, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 47 publications
2
102
0
Order By: Relevance
“…This can be attributed to the fact that it is a naturally produced metabolite of E. coli and that an efflux pump system exists, i.e., AaeA and AaeB, to push out any excess that may build up within the cell. In fact, it has been reported that the addition of 4-hydroxybenzoic acid exogenously results in the up-regulation of the aaeXAB expression levels which encodes for the putative efflux proteins (55). The authors theorized that this efflux system serves as a metabolic relief valve to reduce the toxicity of the compound.…”
Section: Hydroxybenzoic Acids From Lignin Hydrolysismentioning
confidence: 99%
“…This can be attributed to the fact that it is a naturally produced metabolite of E. coli and that an efflux pump system exists, i.e., AaeA and AaeB, to push out any excess that may build up within the cell. In fact, it has been reported that the addition of 4-hydroxybenzoic acid exogenously results in the up-regulation of the aaeXAB expression levels which encodes for the putative efflux proteins (55). The authors theorized that this efflux system serves as a metabolic relief valve to reduce the toxicity of the compound.…”
Section: Hydroxybenzoic Acids From Lignin Hydrolysismentioning
confidence: 99%
“…An active transport of the aromatic out of the cell (Van Dyk et al, 2004) may contribute to achieving these comparatively high titers of extracellular pHBA.…”
Section: Bio-based Production Of Phba and Pabamentioning
confidence: 99%
“…2 Enumeration of EFMs proceeded at a minimum speed of 3,100 modes/sec when using EFMTool and at an average speed of 50,000 modes/sec when using the new FluxModeCalculator (van Klinken & Willems van Dijk, 2015). NExT reached a minimum speed of 120 modes/sec in case of the most complex S. cerevisiae network when relying on the fmincon solver.…”
Section: Network Embedded Thermodynamic Analysis Of Elementary Flux Mmentioning
confidence: 99%
“…It has since been found to be a widespread mechanism in both gram positive and gram negative organisms to expel antibiotics. Efflux pumps also play a major role in extrusion of poorly diffusible endogenous molecules [17,18] and potentially harmful exogenous diffusible substances [19,20] . Resistance nodulation cell division (RND) transporters such as AcrB and its homologues are major multidrug efflux transporters in gram negative bacteria such as E. coli and Pseudomonas aeruginosa [4] .…”
Section: Introductionmentioning
confidence: 99%